PENGARUH GREEN MARKETING, BRAND AWARENESS DAN ATTITUDE TERHADAP PURCHASE INTENTION AIR MINUM DALAM KEMASAN MEREK ADES (Studi pada Masyarakat di Kota Semarang) - Andini, Niar; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to analyze the influence of the green marketing, brand awareness, and attitude on purchase intention bottled water brand Ades. Data were collected in this study through questionnaire method against 100 respondents. The sampling technique used purposive sampling method, sampling technique based on criteria such as knowing brand Ades and live in the city of Semarang. The method of analysis used the analysis of quantitative and qualitative analysis. Quantitative analysis include validity and reliability test, the classic assumption test, hypothesis testing via the F test and t test and the coefficient of determination (R2). Analysis technique used multiple linear regression analysis with SPSS. The results showed that the content of the green marketing, brand awareness, and attitude have a positive and significant impact on purchase intention. Through the F test can be see that the variable independent has a significant jointly on purchase intention. Figures adjusted R square of 0,255 indicates that 25,5 percent the variations of purchase intention can be explained by attitude variable used in the regression equation. While the rest of 74,5 percent is explained by another variables not included in this study.